Control of porphyrin interactions via structural changes of a peptoid scaffold. Issue 45 (9th November 2017) - Yang, Woojin; Kang, Boyeong; Voelz, Vincent A.; Seo, Jiwon
Abstract : A template to control porphyrin interactions is constructed by displaying porphyrins at defined positions on a helical peptoid. Abstract : Nature utilizes optimally organized pigments in light-harvesting complexes. To mimic the natural photosynthetic proteins, effective control over inter-pigment interactions is necessary to attain the desired photophysical properties. Previously, we developed porphyrin–peptoid conjugates (PPCamide ) and displayed two porphyrins at defined positions on an α-helical peptoid using a flexible n -butyl linker. Herein, we synthesized new porphyrin–peptoid conjugates (PPCC–C ), where porphyrins are conjugated through a rigid C–C linkage to the helical peptoid via the Suzuki–Miyaura cross-coupling reaction. With PPCC–C, we studied the effects of backbone conformation, inter-porphyrin distance, and the linker flexibility on porphyrin interactions. When the rigid C–C linkage was used, conformational homogeneity of the PPC increased, providing more effective intramolecular excitonic couplings between the porphyrins; however, the intermolecular porphyrin J-aggregation decreased. In PPCC–C with a nonameric peptoid backbone, the formation of a threaded loop conformation was observed, which could be switched back to a helical conformation by N-terminal acetylation or by the addition of a protic solvent. This threaded loop-to-helix conversion restored the intramolecular porphyrin interactions. Our results suggest that PPCs represent an excellent system for control over porphyrin interactions and therefore are useful as a model system to elucidate pigment interactions in nature or as a molecular construct with switchable photophysical properties.